Assessing Fine-Granularity Structural and Functional Connectivity in Children With Attention Deficit Hyperactivity Disorder - Wang, Peng; Jiang, Xi; Chen, Hanbo; Zhang, Shu; Li, Xiang; Cao, Qingjiu; Sun, Li; Liu, Lu; Yang, Binrang; Wang, Yufeng (Frontiers in Human Neuroscience, 2020)
Attention Deficit Hyperactivity Disorder (ADHD) was considered to be a disorder with high heterogeneity as various abnormalities were found across widespread brain regions in recent neuroimaging studies. However, remarkable individual variability of cortical structure and function may have partially contributed to these discrepant findings. In this work, we applied the DICCCOL (Dense Individualized and Common Connectivity-Based Cortical Landmarks) method to identify fine-granularity corresponding functional cortical regions across different subjects based on the shape of white matter fiber bundle, and measured functional connectivities between these cortical regions. Fiber bundle pattern and functional connectivity were compared between ADHD patients and normal controls in two independent samples. Interestingly, four neighboring DICCCOLs located close to the left parietooccipital area consistently exhibited discrepant fiber bundles in both datasets. The left precentral gyrus (DICCCOL 175, BA 6) and the right anterior cingulate gyrus (DICCCOL 321, BA 32) had the highest connection number among 78 pairs of abnormal functional connectivities with good cross-sample consistency. Furthermore, abnormal functional connectivities were significantly correlated with ADHD symptoms. Our studies revealed novel fine-granularity structural and functional alterations in ADHD.